THE MAIN MODELS OF ELECTORAL SYSTEMS AND SOME EFFECTS FROM THEIR USE: UKRAINIAN CONTEXT - Авксентьєв, А.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The main models of electoral systems and consequences to which brings their use are reseqrched. The main emphasis is placed on the connection of electoral systems with other elements of political system. Domestic experience of application of opposite types of electoral formulas, and also phenomenon of „parlaiment disproportionality" are analyzed. Level of disproportionality of the Verkhovna Rada of Ukraine of 3-7 convocations is compared with the help of „Gallagher’s index".